Prominent T cell response to a selectively in vivo expressed Borrelia burgdorferi outer surface protein (pG) in patients with Lyme disease - Bauer, Yvonne; Hofmann, Heidelore; Jahraus, Oliver; Mytilineos, Joannis; Simon, Markus M.; Wallich, Reinhard (European journal of immunology, 2001)
Diagnosis of Lyme disease by analysis of T cell immune responses in vitro is curtailed by poor correlation between test results and status of infection. This is probably due to the inherent nonspecific activation potential of the causative agent, the spirochete Borrelia burgdorferi, for bystander lymphocytes, in particular via their outer surface lipoproteins. We have now applied a novel protocol to determine specific T cell responses in Lyme disease patients and exclude unrelated cellular responses in vitro. Non-lipidated spirochetal antigens (OspA, OspC and P39) including those selectively expressed in the mammalian host (pG and BapA) were used for antigenic stimulation and autologous dendritic cells served as antigen-presenting cells. The majority of patients with well-defined early and late manifestations of Lyme disease exhibited specific T cell proliferative responses to one or more of the indicated antigens, however at distinct levels. Most notably, among the five antigens tested, pG was specifically recognized by the majority of T cell populations (>70%) - mainly Th1 cells - from patients but not control individuals. These data indicate a causal relationship between B. burgdorferi infection and T cell reactivity to pG, thus making this protein a promising additional diagnostic marker for Lyme disease.
Gesehen am 01.03.2021